Efficacy of artemether–lumefantrine, artesunate–amodiaquine, and dihydroartemisinin–piperaquine for treatment of uncomplicated Plasmodium falciparum malaria in Angola, 2015. (December 2017) - Plucinski, Mateusz; Dimbu, Pedro; Macaia, Aleixo; Ferreira, Carolina; Samutondo, Claudete; Quivinja, Joltim; Afonso, Marília; Kiniffo, Richard; Mbounga, Eliane; Kelley, Julia; Patel, Dhruviben; He, Yun; et al.
Abstract Background Recent anti-malarial resistance monitoring in Angola has shown efficacy of artemether–lumefantrine (AL) in certain sites approaching the key 90% lower limit of efficacy recommended for artemisinin-based combination therapy. In addition, a controversial case of malaria unresponsive to artemisinins was reported in a patient infected in Lunda Sul Province in 2013. Methods During January–June 2015, investigators monitored the clinical and parasitological response of children with uncomplicatedPlasmodium falciparum infection treated with AL, artesunate–amodiaquine (ASAQ), or dihydroartemisinin–piperaquine (DP). The study comprised two treatment arms in each of three provinces: Benguela (AL, ASAQ), Zaire (AL, DP), and Lunda Sul (ASAQ, DP). Samples from treatment failures were analysed for molecular markers of resistance for artemisinin (K13) and lumefantrine (pfmdr1 ). Results A total of 467 children reached a study endpoint. Fifty-four treatment failures were observed: four early treatment failures, 40 re-infections and ten recrudescences. Excluding re-infections, the 28-day microsatellite-corrected efficacy was 96.3% (95% CI 91–100) for AL in Benguela, 99.9% (95–100) for ASAQ in Benguela, 88.1% (81–95) for AL in Zaire, and 100% for ASAQ in Lunda Sul. For DP, the 42-day corrected efficacy was 98.8% (96–100) in Zaire and 100% in Lunda Sul. All treatment failures were wild type for K13, but all AL treatment failures hadpfmdr1 haplotypes associated with decreased lumefantrine susceptibility. Conclusions No evidence was found to corroborate the specific allegation of artemisinin resistance in Lunda Sul. The efficacy below 90% of AL in Zaire matches findings from 2013 from the same site. Further monitoring, particularly including measurement of lumefantrine blood levels, is recommended.